Zeichen der Einheit: Eucharistiegemeinschaft ökumenischer Paare - Knop, Julia (Catholica <Münster>, 2018)
The document "Walking with Christ - Tracing Unity11 was published as Orientation text in June 2018 fol/owing serious debates. lt translates the existing norms of Eucharistie communion into concrete guidance for Christians of other denominations who are married to a Catholic. The document is mainly conventiona/, but prepares the way for further steps towards ecumenica/ communion.